Therapeutic but Not Therapy: Using Critical Spirituality to Engage with Traumatic Experiences - Gardner, Fiona 1950- (2022)
Participants in critical reflection workshops and peer supervision often comment that the process feels therapeutic, enabling them to engage with challenging experiences, even although it is clearly not therapy. This reflective article explores these comments, particularly how the processes of critical reflection embedded in critical spirituality can foster a deep exploration of traumatic experiences that undermine the sense of self and the ability to act with agency. While spirituality is broadly defined as that which gives life meaning including a sense of the transcendent, the ‘critical’ aspect includes the influence of the person’s own and the broader social context. Using two participant examples for illustration, key aspects of the process are identified: unearthing and naming deeply held, limiting and often longstanding assumptions influencing the person’s sense of who they are and how they operate. Next, understanding the prevailing social context can generate liberating new perspectives. Asking what is meaningful and why given the person’s spirituality can foster new, freeing and enabling assumptions, values and beliefs and experimenting with new ways of being and acting. What often emerges is that participants come to recognise the depth of meaning that transforms their perception of their experience and sense of themselves.
Keywords: therapeutic; Meaning; critical spirituality; critical reflection